Artificial rupture of membranes as a mode for induction of labor in women with a previous cesarean section- a retrospective cohort study - Aharon Dick; Einat Gutman-Ido; Henry Hillel Chill; Gilad Karavani; Ina Ryvkin; Shay Porat; Joshua Isaac Rosenbloom (BMC Pregnancy and Childbirth, 2022)
Abstract Background Induction of labor in women with a previous cesarean section (CS) is associated with increased rates of uterine rupture and failed attempt for vaginal delivery. Prostaglandins use is contraindicated in this population, limiting available options for cervical ripening. Objective To evaluate the efficacy and safety of artificial rupture of membranes (AROM) as a mode of Induction of labor (IOL) in women with a previous cesarean section. Methods A retrospective cohort study conducted in a single tertiary care center between January 2015 and October 2020. Women with one previous cesarean section and a current singleton term pregnancy requiring IOL, with an unfavorable cervix, were included. The primary outcome was a successful vaginal delivery (VBAC); secondary outcomes were rates of chorioamnionitis, uterine rupture and low Apgar score (< 7). Results Of the 665 women who met the inclusion criteria, 492 (74%) did not receive subsequent oxytocin and 173 (26%) did. There were significant differences in the baseline characteristics between these two groups, including maternal age, cervical dilation at presentation, parity, and a history of a previous VBAC. Among women who were induced solely by AROM the rate of a successful TOLAC was higher (81.3% vs 73.9%), total time of IOL was shorter (mean 8.7 h vs.16.1 h) and the risk of chorioamnionitis was lower (7.3% vs 18.4%). When subdividing the women who received oxytocin into early (< 12 h after AROM) vs late (> 12 h after AROM) administration, there were no significant changes in the rates of successful VBAC or of chorioamnionitis. Conclusion AROM as a single mode of IOL in women with a previous CS is a safe and efficient practice with high rates of successful VBAC. When spontaneous labor does not develop, there is no advantage to delay the administration of oxytocin.